Dampak Kesadaran Energi Terhadap Perilaku Konsumsi Dan Strategi Penghematan - Alexander Panjaitan, Andrew; Adnan Putra Ramadhan, Muhamad; Maulana Asshidqi, Muhammad; Cindrakusuma, Ryan; Winarno, Tri; Tua Natalis Situmorang, Marningot (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Public energy awareness is a key factor in driving energy conservation and the transition to renewable energy. However, the level of awareness is influenced by various factors, including socio-demographics, energy literacy, and the effectiveness of government policies. This study aims to analyze the relationship between energy awareness and energy consumption behavior and effective strategies to improve it. This study uses a literature review method by analyzing 15 articles published between 2020–2024 from Google Scholar. Selection criteria include the relevance of the title, year of publication, and focus on energy awareness. Data are reviewed thematically to identify patterns and policy recommendations. Energy awareness is positively correlated with energy saving behavior, especially in individuals with high energy literacy. Socio-demographic factors such as education, income, age, and geographic location influence the level of awareness. Younger generations and urban communities are more responsive to clean energy campaigns, while low-income groups face challenges in accessing technology. Government policies such as solar panel subsidies, energy efficiency regulations, and education programs have proven effective if supported by community participation and an inclusive approach. Increasing energy awareness requires a multidimensional strategy, including: (1) formal and informal education, (2) creative media-based campaigns, (3) targeted incentives, and (4) collaboration between stakeholders. Policy implications include simplifying bureaucracy for renewable energy and integrating energy literacy into the national curriculum.